PERBANDINGAN UJI DETEKSI FORMALIN DALAM DAGING AYAM MENGGUNAKAN FENILHIDRAZIN DAN QUANTOFIX - , DEWI INTAN JELITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chicken is one of the contributors foodstuffs of animal protein which is consumed by community. eventhough this animal protein is important as source of nutrition, this product can be dangerous if it contain non-food preservative. Nowdays formalin one of non-food preservative which is now widely used is formalin. The aim of the research is to know thee differenees qualitative fenilhidrazin test and quantofix to detect formalin in the chicken with various contretation. There is 20 sample of chicken that use as sample. Every sample tested using fenilhidrazin and quantofix. On each trial consisted of 11, one trial without formalin, and asample which is soaked formalin with concreation 0, 005%, 0, 010%, 0,015%, 0,020%, 0,025%, 0,030%, 0,035%, 0,040%, 0,045% and 0,050% for 2 hours. Each tested twice. The positive results of formalin the test with fenilhidrazin (shown in green), and quantofix (shown in violet). The results obtained show positive result 100% for test formalin used fenilhidrazin and 80% positive result formalin test using quantofix. Based on the intensity of the color which is produced, the formalin test in the detection of chicken which is more sensitive is fenilhidrazin.